Structure, process and outcomes of chest pain units established in the ESCAPE Trial. Issue 7 (20th June 2007) - Arnold, Jane; Goodacre, Steve; Morris, Francis
Abstract : Background: Chest pain units (CPUs) provide a system of care for patients with acute chest pain that can improve outcomes while reducing health service costs. The Effectiveness and Safety of Chest Pain Assessment to Prevent Emergency Admissions (ESCAPE) multicentre trial was undertaken to determine whether CPUs could be successfully established throughout the National Health Service (NHS). Aim: To describe the structure, processes and outcomes of patients managed by CPUs in the ESCAPE Trial. Method: 7 of 14 participating hospitals were randomly allocated to establish CPU care. Each hospital set up a CPU using standardised protocols to provide biochemical cardiac marker and exercise treadmill testing for low-risk patients. Research staff then followed up patients for 30 days to identify any adverse events, defined as chest pain-related readmission to hospital for more than 48 h, non-fatal myocardial infarction and all deaths. Results: The 7 units managed a total of 1644 patients during their first year of operation. Activity varied from 1 to 7 patients per 1000 adult emergency department attendances. Overall, 1374 (83%) patients were discharged after CPU assessment, with 23 (1.7%) adverse events recorded among those discharged. Some, but not all, of the variation in activity could be attributed to hospital size and patient selection. Conclusion: CPU care can be instituted in a safe manner at a variety of NHS hospitals, with most patients being discharged after assessment. However, there is variation in the number and type of patients managed by the different units. Further research is required to identify reasons for variation in CPU activity.